Interreligious comparisons in religious studies and theology: comparison revisited - Schmidt-Leukel, Perry; Nehring, Andreas (Bloomsbury, 2016)
Contributors -- Acknowledgements -- Introduction / Perry Schmidt-Leukel and Andreas Nehring -- Part I. Comparison: Contestation and Defence. Chapter 1. Comparative Methodology and the Religious Studies Toolkit / Paul Hedges ; Chapter 2. Comparison in the Maelstrom of Historicity: A Postcolonial Perspective on Comparative Religion / Michael Bergunder ; Chapter 3. Modes of Comparison: Towards Creating a Methodological Framework for Comparative Studies / Oliver Freiberger ; Chapter 4. Comparison as a Necessary Evil: Examples from Indian and Jewish Worlds / Philippe Bornet -- Part II. Phenomenology and the Foundations of Comparison. Chapter 5. Camouflage of the Sacred: Can We Still Branch Off from Eliade's Comparative Approach? / Andreas Nehring ; Chapter 6. The Singular and the Shared: Making Amends to Eliade after the Dismissal of the Sacred / Kenneth Rose ; Chapter 7. Religious Practice and the Nature of the Human / Gavin Flood ; Chapter 8. On All-Embracing Mental Structures: Towards a Transcendental Hermeneutics of Religion / Fabian Völker -- Part III. Reciprocal Illumination and Comparative Theology. Chapter 9. Comparative Theology and Comparative Religion / Klaus von Stosch ; Chapter 10. Reciprocal Illumination / Arvind Sharma ; Chapter 11. On Creativity, Participation and Normativity: Comparative Theology in Discussion with Arvind Sharma's Reciprocal Illumination / Ulrich Winkler ; Chapter 12. Christ as Bodhisattva: A Case of Reciprocal Illumination / Perry Schmidt-Leukel -- Index.